Gang Organization and Gang Identity: An Investigation of Enduring Gang Membership - Leverso, John (Journal of quantitative criminology, 2019)
Motivated by recent advances in the study of disengagement from street gangs, this research develops a theoretical framework of enduring gang membership based on gang organization and gang identity. Using multivariate data, this research tests the theoretical framework against a competing theory derived from the general theory of crime where gang organization and gang identity are non-existent or unimportant in producing enduring gang membership.